How does COVID-19 pandemic affect entrepreneur anxiety? The role of threat perception and performance pressure - Li, Yunjian; Chen, Hongchuan; Liu, Chunzhen; Liu, Hong (Frontiers in Psychology, 2022)
The mental health of the entrepreneur decides whether the entrepreneurial firm can make the right decision, which is related to the healthy development of the entrepreneurial firms. Based on the event system theory and the cognitive appraisal theory, this paper explores the effect of COVID-19 pandemic on the entrepreneur anxiety, and the threat perception and performance pressure are introduced to investigate the mediating mechanism and boundary of this effect. Using the survey data of 168 entrepreneurs for empirical testing, the research results are as follows. First, the COVID-19 pandemic significantly positively affects entrepreneur anxiety. Second, the entrepreneur threat perception plays a mediating role between the COVID-19 pandemic and the entrepreneur anxiety, which means the COVID-19 pandemic can enhance the external threat perception of entrepreneurs, and then affect the entrepreneur anxiety. Third, the positive effect of the COVID-19 pandemic on the entrepreneur anxiety is strengthened by the entrepreneur performance pressure, while the positive effect of entrepreneur threat perception on entrepreneur anxiety is weakened by the entrepreneur performance pressure. The above findings are helpful to explore the mechanism of the COVID-19 pandemic and other critical crisis events on entrepreneurs’ mental health, and provide enlightenments for the intervention of entrepreneurs’ mental health.